2013
DOI: 10.1007/s00253-013-5000-0
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of the lipopeptides produced by Bacillus amyloliquefaciens anti-CA against Candida albicans isolated from clinic

Abstract: The bacterium Bacillus amyloliquefaciens anti-CA isolated from mangrove system was found to be able to actively kill Candida albicans isolated from clinic. The bacterial strain anti-CA could produce high level of bioactive substance, amylase and protease in the cheap medium containing 2.0 % soybean meal, 2.0 % wheat flour, pH 6.5 within 26 h. After purification, the main bioactive substance was confirmed to be a cyclic lipopeptide containing a heptapeptide, L-Asp→L-Leu→L-Leu→L-Val→L-Val→L-Glu→L-Leu and a 3-OH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 23 publications
0
28
0
Order By: Relevance
“…The main bioactive substance was a cyclic lipopeptide containing a heptapeptide, AspLeuLeuValValGluLeu, and a 3-OH fatty acid with 15 carbon atoms. The lipopeptide also killed other yeast strains including Candida tropicalis, Metschnikowia bicuspidate, Saccharomyces cerevisiae , and Yarrowia lipolytica (Song et al 2013). …”
Section: Antifungal Productsmentioning
confidence: 99%
“…The main bioactive substance was a cyclic lipopeptide containing a heptapeptide, AspLeuLeuValValGluLeu, and a 3-OH fatty acid with 15 carbon atoms. The lipopeptide also killed other yeast strains including Candida tropicalis, Metschnikowia bicuspidate, Saccharomyces cerevisiae , and Yarrowia lipolytica (Song et al 2013). …”
Section: Antifungal Productsmentioning
confidence: 99%
“…Fengycin and iturin exhibit high antifungal activities against numerous phytopathogens. Surfactin is mostly known for its strong antibacterial and antiviral activities[8]. …”
Section: Introductionmentioning
confidence: 99%
“…strain H 9/15: Results of the study revealed that H 9/15 produced 2,4-diacetylphloroglucinol (2,4-DAPG) with the signal similar to pure 2,4-DAPG at a retention time of 13 min (Fig 3). 2,4-DAPG has been shown to play a role in the control of numerous fungal pathogens including S. rolfsii (Raaijmakers et al, 2002;Song et al, 2013). The DAPG-producing rhizobacteria were also reported to promote plant growth and inhibit S. rolfsii, Aspergillus flavus and A. niger (Sherathia et al 2016).…”
Section: Biological Control Of Stem Rot By Antagonistic Bacteriamentioning
confidence: 99%